The use of pocket books in improving knowledge of tetanus toxoid immunization among adolescents - Endriati, Endra; Laman, Aspia; Damayanti, Dini Fitri (ELECTRON (Journal of Science and Technology), 2025)
Tetanus Toxoid (TT) immunization is crucial for protecting adolescents, especially prospective brides, from tetanus infection. Adequate knowledge about TT immunization can increase participation in immunization programs and reduce maternal and infant mortality. This study aimed to determine the effectiveness of pocket books in improving adolescents’ knowledge about TT immunization at Santo Benediktus Pahauman High School. A quantitative quasi-experimental design with a one-group pretest–posttest approach was used, involving 120 respondents selected through total sampling. Knowledge levels were measured using questionnaires before and after the intervention. The results showed a significant increase in knowledge, with the average score rising from 7.50 (range 3–14) before the intervention to 18.42 (range 15–20) after using the pocket book (p < 0.05). These findings indicate that pocket books are effective educational media for improving adolescents’ understanding of TT immunization. In conclusion, pocket books can be utilized as an effective tool in health education to promote immunization awareness among adolescents.